Correlating the global Cambrian-Ordovician boundary: Precise comparison of the Xiaoyangqiao section, Dayangcha, North China with the Green Point GSSP section, Newfoundland, Canada - Wang, Xiao-Feng; Stouge, Svend; Maletz, Joerg; Bagnoli, Gabriella; Qi, Yu-Ping; Raevskaya, Elena G.; Wang, Chuan-Shang; Yan, Chun-Bo (Palaeoworld, 2019)
The Cambrian-Ordovician boundary interval exposed at the Xiaoyangqiao section, North China is presented. The distribution of stratigraphically important fossils in the Xiaoyangqiao section revealed several nearly coeval graptolite, conodont, trilobite, and acritarch bioevents in the uppermost Cambrian-lowermost Ordovician carbonate-siliciclastic sedimentary sequence. The precise correlation to the Green Point GSSP section, western Newfoundland, Canada allows for the identification of the corresponding GSSP level in the Xiaoyangqiao section. The combined data from the Xiaoyangqiao section and the Green Point GSSP section provide a series of events that all can be applied as proxies for identification of the Cambrian-Ordovician boundary horizon outside the GSSP. Based on this, the Xiaoyangqiao section, Dayangcha, is here strongly recommended as a candidate for an Auxiliary Boundary Stratigraphic Section and Point section (ASSP) for the base of the Ordovician System, because it provides one of the best and most complete Cambrian-Ordovician transitions in the world and because the first planktic graptolites are from the Xiaoyangqiao section. (C) 2019 Elsevier Ireland Ltd Elsevier B.V. and Nanjing Institute of Geology and Palaeontology, CAS. Published by Elsevier B.V. All rights reserved.